7. Trigonometrical Ratios of Angle and Sign SolutionsΒΆ

  1. Let us solve these one by one:

    1. \(\cos 2A = \cos 60^\circ = \frac{1}{2}\)

      \(\cos^2A - \sin^2A = \left(\frac{\sqrt{3}}{2}\right)^2 - \left(\frac{1}{2}\right)^2 = \frac{3}{4} - \frac{1}{4} = \frac{1}{2}\)

      \(2\cos^2 - 1 = 2.\left(\frac{\sqrt{3}}{2}\right)^2 - 1 = 2.\frac{3}{4} - 1 = \frac{1}{2}\)

    2. \(\sin 2A = \sin 60^\circ = \frac{\sqrt{3}}{2}\)

      \(2\sin A\cos A = 2.\frac{1}{2}.\frac{\sqrt{3}}{2} = \frac{\sqrt{3}}{2}\)

    3. \(\cos 3A = \cos 90^\circ = 0\)

      \(4\cos^3A - 3\cos A = 4.\frac{3\sqrt{3}}{8} - 3\frac{\sqrt{3}}{2} = 0\)

    4. \(\sin 3A = \sin 90^\circ = 1\)

      \(3\sin A - 4\sin^3 A = 3\frac{1}{2} - 4. \frac{1}{2^3} = \frac{3}{2} - \frac{1}{2} = 1\)

    5. \(\tan 2A = \tan 60^\circ = \sqrt{3}\)

      \(\frac{2\tan A}{1 - \tan^2A} = \frac{2.\frac{1}{\sqrt{3}}}{1 - \frac{1}{3}} = \frac{2}{\sqrt{3}}.\frac{3}{2} = \sqrt{3}\)

  2. Let us solve these one by one:

    1. \(\sin 2A = \sin 90^\circ = 1\)

      \(2\sin A\cos A = 2\sin 45^\circ\cos 45^\circ = 2.\frac{1}{\sqrt{2}}.\frac{1}{\sqrt{2}} = 1\)

    2. \(\cos 2A = \cos 90^\circ = 0\)

      \(1 - 2\sin^2A = 1 - 2\sin^245^\circ = 1 - 2.\frac{1}{(\sqrt{2})^2} = 1 - 2.\frac{1}{2} = 0\)

    3. \(\tan 2A = \tan 90^\circ = \infty\)

      \(\frac{2\tan A}{1 - \tan^2A} = \frac{2.1}{1 - 1^2} = \frac{2}{0} = \infty\)

  3. L.H.S. \(= \sin^230^\circ + \sin^245^\circ + \sin^260^\circ\)

    \(= \frac{1}{2^2} + \frac{1}{(\sqrt{2})^2} + \frac{(\sqrt{3})^2}{2^2} = \frac{1}{4} + \frac{1}{2} + \frac{3}{4} = \frac{3}{2} =\) R.H.S.

  4. L.H.S. \(= \tan^230^\circ + \tan^245^\circ + \tan^260^\circ\)

    \(= \frac{1}{(\sqrt{3})^2} + 1 + (\sqrt{3})^2 = \frac{1}{3} + 1 + 3 = 4\frac{1}{3} =\) R.H.S.

  5. L.H.S. \(= \sin 30^\circ\cos 60^\circ + \sin 60^\circ\cos 30^\circ\)

    \(= \frac{1}{2}\frac{1}{2} + \frac{\sqrt{3}}{2}\frac{\sqrt{3}}{2} = \frac{1}{4} + \frac{3}{4} = 1 =\) R.H.S.

  6. L.H.S. \(= \cos 45^\circ\cos 60^\circ - \sin 45^\circ\sin 60^\circ\)

    \(= \frac{1}{\sqrt{2}}\frac{1}{2} - \frac{1}{\sqrt{2}}\frac{\sqrt{3}}{2} = \frac{1}{2\sqrt{2}} - \frac{\sqrt{3}}{2\sqrt{2}}\)

    \(= \frac{1 - \sqrt{3}}{2\sqrt{2}} = - \frac{\sqrt{3} - 1}{2\sqrt{2}} =\) R.H.S.

  7. L.H.S. \(= \cosec^245^\circ.\sec^230^\circ.\sin^290^\circ.\cos 60^\circ\)

    \(= (\sqrt{2})^2.\frac{2^2}{(\sqrt{3})^2}.1^2.\frac{1}{2} = 2.\frac{4}{3}.1.\frac{1}{2} = \frac{4}{3} =\) R.H.S.

  8. L.H.S. \(= 4\cot^245^\circ-\sec^260^\circ + \sin^230^\circ\)

    \(= 4.1^2 - 2^2 + \frac{1}{2^2} = 4 - 4 + \frac{1}{4} = \frac{1}{4} =\) R.H.S.

  9. L.H.S. \(= \sin 420^\circ\cos 390^\circ + \cos(-300^\circ)\sin(-330^\circ)\)

    \(= \sin(360^\circ + 60^\circ)\cos(360^\circ + 30^\circ) + \cos 60^\circ\sin30^\circ\)

    \(= \sin 60\cos30^\circ + \cos 60^\circ\sin30^\circ = \frac{\sqrt{3}}{2}.\frac{\sqrt{3}}{3} + \frac{1}{2}.\frac{1}{2} = \frac{3}{4} + \frac{1}{4} = 1 =\) R.H.S.

  10. L.H.S. \(= \cos 570^\circ\sin 510^\circ -\sin 330^\circ\cos 390^\circ\)

    \(= \cos(360^\circ + 210^\circ)\sin(360^\circ + 150^\circ) - \sin(360^\circ - 30^\circ)\cos(360^\circ + 30^\circ)\)

    \(= \cos(180^\circ + 30^\circ)\sin(180^\circ - 30^\circ) + \sin 30^\circ\cos 30^\circ\)

    \(= -\cos 30^\circ\sin 30^\circ + \sin 30^\circ\cos 30^\circ\)

    \(= 0 =\) R.H.S.

  11. \(\cos \frac{\pi}{3} - \sin \frac{\pi}{3} = \frac{1}{2} - \frac{\sqrt{3}}{2} = \frac{1 - \sqrt{3}}{2}\)

    \(\tan\frac{\pi}{3} + \cot\frac{\pi}{3} = \sqrt{3}. + \frac{1}{\sqrt{3}} = \frac{4}{\sqrt{3}}\)

  12. \(\cos\frac{2\pi}{3} -\sin\frac{2\pi}{3} = \cos\left(\pi - \frac{\pi}{3})\right) - \sin\left(\pi - \frac{\pi}{3}\right)\)

    \(= -\cos \frac{\pi}{3} - \sin\frac{\pi}{3} = -\frac{1}{2} - \frac{\sqrt{3}}{2} = - \frac{1 + \sqrt{3}}{2}\)

    \(\tan\frac{2\pi}{3} + \cot\frac{2\pi}{3} = \tan\left(\pi - \frac{\pi}{3}\right) + \cot\left(\pi - \frac{\pi}{3}\right)\)

    \(= -\tan \frac{\pi}{3}. -\cot \frac{\pi}{3} = -\sqrt{3} - \frac{1}{\sqrt{3}} = -\frac{4}{\sqrt{3}}\)

  13. \(\cos\frac{5\pi}{4} - \sin\frac{5\pi}{4} = \cos\left(\pi + \frac{\pi}{4}\right) + \sin \left(\pi + \frac{\pi}{4}\right)\)

    \(= -\cos \frac{\pi}{4} - \sin \frac{\pi}{4} = -\frac{1}{\sqrt{2}} - \frac{1}{\sqrt{2}} = -\sqrt{2}\)

    \(\tan \frac{5\pi}{4} + \cot \frac{5\pi}{4} = \tan\left(\pi + \frac{\pi}{4}\right) + \cot\left(\pi + \frac{\pi}{4}\right)\)

    \(= \tan \frac{\pi}{4} + \cot \frac{\pi}{4} = 1 + 1 = 2\)

  14. \(\cos\frac{7\pi}{4} + \cos\frac{7\pi}{4} = \cos \left(\pi + \frac{3\pi}{4}\right) + \sin\left(\pi + \frac{3\pi}{4}\right)\)

    \(= -\cos\frac{3\pi}{4} - \sin\frac{3\pi}{4} = -\cos\left(\pi - \frac{\pi}{4}\right) -\sin \left(\pi - \frac{\pi}{4}\right)\)

    \(= \cos \frac{\pi}{4} -\sin \frac{\pi}{4} = \frac{1}{\sqrt{2}} - \frac{1}{\sqrt{2}} = 0\)

    \(\tan \frac{7\pi}{4} + \cos \frac{7\pi}{4} = \tan\left(\pi + \frac{3\pi}{4}\right) + \cos \left(\pi + \frac{3\pi}{4}\right)\)

    \(= \tan \frac{3\pi}{4} + \cot \frac{3\pi}{4} = \tan\left(\pi - \frac{\pi}{4}\right) + \cot \left(\pi - \frac{\pi}{4}\right)\)

    \(= -\tan \frac{\pi}{4} - \tan \frac{\pi}{4} = -2\)

  15. \(\cos\frac{11\pi}{3} + \sin \frac{11\pi}{3} = \cos\left(2\pi + \pi + \frac{2\pi}{3}\right) + \sin\left(2\pi + \pi + \frac{2\pi}{3}\right)\)

    \(= \cos\left(\pi + \frac{2\pi}{3}\right) + \sin \left(\pi + \frac{2\pi}{3}\right) = -\cos\frac{2\pi}{3} - \sin\frac{2\pi}{3}\)

    \(= -\cos\left(\pi - \frac{\pi}{3}\right) - \sin\left(\pi - \frac{\pi}{3}\right)\)

    \(=\cos \frac{\pi}{3} -\sin \frac{\pi}{3} = \frac{1 - \sqrt{3}}{2}\)

    \(\tan\frac{11\pi}{3} + \cot\frac{11\pi}{3} = \tan\left(2\pi + \pi + \frac{2\pi}{3}\right) + \cot\left(2\pi + \pi + \frac{2\pi}{3}\right)\)

    \(= \tan\left(\pi + \frac{2\pi}{3}\right) + \cot\left(\pi + \frac{2\pi}{3}\right)\)

    \(= \tan\frac{2\pi}{3} + \cot\frac{2\pi}{3} = \tan\left(\pi - \frac{\pi}{3}\right) + \cot(\pi - \frac{\pi}{3})\)

    \(= -\tan\frac{\pi}{3} -\cot\frac{\pi}{3} = -\sqrt{3} - \frac{1}{\sqrt{3}} = - \frac{4}{\sqrt{3}}\)

  16. \(\sin\) of an angle is positive in first and second quadrant. Also, \(\sin 45^\circ = \frac{1}{\sqrt{2}},\) therefore the angles will be \(45^\circ\) and \(135^\circ.\)

  17. \(\cos\) of an angle is positive in second and third quadrant. Also, \(\cos 60^\circ = \frac{1}{2},\) therefore the angles will be \(120^\circ\) and \(240^\circ.\)

  18. \(\tan\) of an angle is negative in second and fourth quadrant. Also, \(\tan 45^\circ = 1,\) therefore the angles will be \(135^\circ\) and \(315^\circ.\)

  19. \(\cot\) of an angle is negative in second and fourth quadrant. Also, \(\cot 30^\circ = \sqrt{3},\) therefore the angles will be \(150^\circ\) and \(330^\circ.\)

  20. \(\sec\) of an angle is negative in second and third quadrant. Also, \(\sec 30^\circ = \frac{2}{\sqrt{3}},\) therefore the angles will be \(150^\circ\) and \(210^\circ.\)

  21. \(\cosec\) of an angle is negative in third and fourth quadrant. Also, \(\cosec 30^\circ = 2,\) therefore the angles will be \(210^\circ\) and \(330^\circ.\)

  22. \(\sin(-65^\circ) = -\sin 65^\circ = -\cos(90^\circ - 65^\circ) = -\cos 25^\circ\)

  23. \(\cos(-84^\circ) = \cos 84^\circ = \sin(90^\circ - 84^\circ) = \sin 6^\circ\)

  24. \(\tan(137^\circ) = \tan(180^\circ - 43^\circ) = -\tan 43^\circ\)

  25. \(\sin(168^\circ) = \sin(180^\circ - 12^\circ) = \sin 12^\circ\)

  26. \(\cos(287^\circ) = \cos(180 + 107^\circ) = -\cos 107^\circ = \sin 17^\circ\)

  27. \(\tan(-246^\circ) = -\tan(246^\circ) = -\tan(180 + 66^\circ) = -\tan 66^\circ = -\tan(90^\circ - 24^\circ) = -\cot 24^\circ\)

  28. \(\sin 843^\circ = \sin(2*360^\circ + 123^\circ) = \sin(123^\circ) = \sin(90^\circ + 33^\circ) = \cos 33^\circ\)

  29. \(\cos(-928^\circ) = \cos(2*360^\circ + 208^\circ) = \cos(180^\circ + 28^\circ) = -\cos 28^\circ\)

  30. \(\tan 1145^\circ = \tan(3*360^\circ + 65^\circ) = \tan(65^\circ) = \tan(90^\circ - 25^\circ) = \cot 25^\circ\)

  31. \(\cos 1410^\circ = \cos(360*3 + 330^\circ) = \cos(180^ + 180^\circ - 30^\circ) = \cos 40^\circ\)

  32. \(\cot(-1054^\circ) = -\cot(3*360 - 26^\circ) = \cot 26^\circ\)

  33. \(\sec 1327^\circ = \sec(3*360^\circ + 247^\circ) = \sec(180^\circ + 67^\circ) = -\sec 67^\circ = -\sec(90^\circ - 23^\circ) = -\cosec 23^\circ\)

  34. \(\cosec (-756^\circ) = -\cosec(2*360^\circ + 36^\circ) = -\cosec 36^\circ\)

  35. \(\sin 140^\circ + \cos 140^\circ = \sin(90^\circ + 50^\circ) + \cos(180^\circ - 40^\circ) = \cos 50^\circ - \cos 40^\circ\)

    \(\cos 40^\circ > \cos 50^\circ\) therefore sign will be negative.

  36. \(\sin 278^\circ + \cos 278^\circ = \sin(180^\circ + 98^\circ) + \cos(180^\circ + 98^\circ)\)

    \(= -\sin(98^\circ) - \cos(98^\circ) = -\cos 8^\circ + \cos 82^\circ\)

    \(\cos 8^\circ > \cos 82^\circ\) therefore sign will be negative.

  37. \(\sin(-356^\circ) + \cos(-356^\circ) = -\sin(180^\circ + 180^\circ - 4^\circ) + \cos(180^\circ + 180^\circ - 4^\circ)\)

    \(\sin 4^\circ + \cos 4^\circ\) which will yield a positive sign.

  38. \(\sin(-1125^\circ) + \cos(-1125^\circ) = -\sin(3*360^\circ + 45^\circ) + \cos(3*360^\circ + 445^\circ)\)

    \(= -\sin 45^\circ + \cos 45^\circ = 0\) which is neither negative nor positive.

  39. \(\sin 215^\circ - \cos 215^\circ = \sin(180^\circ + 35^\circ) - \cos(180^\circ + 35^\circ)\)

    \(= -\sin 35^\circ + \cos 35^\circ\)

    \(\because \cos 35^\circ > \sin 35^\circ\) the sign will be positive.

  40. \(\sin 825^\circ - \cos 825^\circ = \sin(2*360^\circ + 105^\circ) - \cos(2*360 + 105^\circ)\)

    \(= \cos 15^\circ + \sin 15^\circ\) for which sign will be positive.

  41. \(\sin(-634^\circ) - \cos(-634)^\circ = -\sin (360^\circ + 274^\circ) - \cos (360^\circ + 274^\circ)\)

    \(= -\sin(180^\circ + 90^\circ + 4^\circ) - \cos(180^\circ + 90^\circ + 4^\circ)\)

    \(= \cos 4^\circ - \sin 4^\circ\) whic will have positive sign.

  42. \(\sin(-457^\circ) - \cos(-457^\circ) = -\sin(360^\circ + 90^\circ + 7^\circ) -\cos(360^\circ + 90^\circ + 7^\circ)\)

    \(=-\cos 7^\circ + \sin 7^\circ\) which will have negative sign.

  43. \(\cos 135^\circ = -\frac{1}{\sqrt{2}}\) then given \(\tan A = -\frac{1}{\sqrt{2}}\)

    \(\sin A = \pm \frac{1}{\sqrt{3}}, \cos A = \pm \frac{\sqrt{2}}{\sqrt{3}}\)

  44. \(\sin(270^\circ + A) = \sin(180^\circ + 90^\circ + A) = -\sin(90^\circ + A) = -\cos A\)

    \(\tan(270^\circ + A) = \tan(180^\circ + 90^\circ + A) = \tan(90^\circ + A) = -\cot A\)

  45. \(\cos(270^\circ - A) = \cos(180^\circ + 90^\circ - A) = -\cos(90^\circ - A) = -\sin A\)

    \(\cot(270^\circ - A) = \cot(180^\circ + 90^\circ - A) = \cot(90^\circ - A) = \tan A\)

  46. L.H.S. \(= \cos A + \sin(270^\circ + A) - \sin(270^\circ - A) + \cos(180^\circ + A)\)

    Using results from previous problems we get

    \(= \cos A + -\cos A + \cos A - \cos A = 0\)

  47. L.H.S. \(= \sec(270^\circ - A)\sec(90^\circ - A) - \tan(270^\circ - A)\tan(90^\circ + A) + 1\)

    \(= \sec(180^\circ + 90^\circ - A)\cosec A + \tan(180^\circ + 90^\circ - A)\cot A + 1\)

    \(= -\cosec^2A + \cot^2A + 1 = -1 + 1 = 0 =\) R.H.S.

  48. L.H.S. \(= \cot A + \tan(180^\circ + A) + \tan(90^\circ + A) + \tan(360^\circ - A)\)

    \(= \cot A + \tan A - \cot A - \tan A = 0 =\) R.H.S.

  49. Given, \(3\tan^245^\circ - \sin^260^\circ - \frac{1}{2}\cot^230^\circ + \frac{1}{8}\sec^245^\circ\)

    \(= 3.1^2 - \left(\frac{\sqrt{3}}{2}\right)^2 - \frac{1}{2}(\sqrt{3})^2 + \frac{1}{8}(\sqrt{2})^2\)

    \(= 3 - \frac{3}{4} - \frac{3}{2} + \frac{2}{8} = 1\)

  50. Given, \(= \frac{\sin(2\pi - 60^\circ).\tan(2\pi - 30^\circ).\sec(2\pi + 60^\circ)}{\tan(\pi - 45^\circ).\sin(\pi + 30^\circ).\sec(2\pi - 45^\circ)}\)

    \(= \frac{-\sin 6-^\circ. -\tan 30^\circ.\sec 60^\circ}{-\tan 45^\circ. -\sin 30^\circ.\sec 45^\circ}\)

    \(= \frac{\frac{\sqrt{3}}{2}.\frac{1}{\sqrt{3}}.2}{1.\frac{1}{\sqrt{2}}.\sqrt{2}} = \sqrt{2}\)

  51. L.H.S. \(= \tan 1^\circ\tan 2^\circ \ldots \tan 89^\circ\)

    \(= (\tan 1^\circ.\tan(90^\circ - 1^\circ).(\tan 2^\circ.\tan(90^\circ - 2^\circ).\ldots.(\tan 44^\circ.\tan(90^\circ - 44^\circ).\tan 45^\circ\)

    \(= (\tan 1^\circ.\cot 1^\circ).(\tan 2^\circ.\cot 2^\circ).\ldots.(\tan 44^\circ.\cot 44^\circ).1\)

    \(= 1.1.\ldots 1.1 [\because \tan\theta\cot\theta = 1]\)

    \(= 1 =\) R.H.S.

  52. L.H.S. \(=(\sin^25^\circ + \sin^285^\circ) + (\sin^210^\circ + \sin^280^\circ) + \ldots + (\sin^240^\circ + \sin^250^\circ) + \sin^245^\circ + \sin^290^\circ\)

    \(= (\sin^25^\circ + \cos^25^\circ) + (\sin^210^\circ + \cos^210^\circ) + \ldots + (\sin^240^\circ + \cos^240^\circ) + \sin^245^\circ + \sin^290^\circ\)

    \(= 1 + 1 +~\text{8 times}+ \left(\frac{1}{\sqrt{2}}\right)^2 + 1 = 9\frac{1}{2} =\) R.H.S.

  53. Given expression can be rewritten as \(= \cos^2 \frac{\pi}{16} + \cos^2 \frac{3\pi}{16} + \cos^2\left(\frac{\pi}{2} - \frac{3\pi}{16}\right) + \cos^2\left(\frac{\pi}{2} - \frac{\pi}{16}\right)\)

    \(= \cos^2 \frac{\pi}{16} + \cos^2 \frac{3\pi}{16} + \sin^2\frac{3\pi}{16} + \sin^2\frac{\pi}{16}\)

    \(= 1 + 1 = 2\)

  54. Substituting the values \(\left(\frac{2}{\sqrt{3}}\right)^2(\sqrt{2})^2 + (\sqrt{3})^2.1^2\)

    \(= \frac{4}{3}.2 + 3 = \frac{17}{3}\)

  55. Substituting the values \((\sqrt{3})^2 - 2.\frac{1}{2^2} - \frac{3}{4}\frac{1}{(\sqrt{2})^2} - 4.\frac{1}{2^2}\)

    \(= \frac{9}{8}\)

  56. Given expression is \(\frac{\sec\circ(2\pi + 120^\circ).\cosec(2\pi + 210^\circ).\tan(2\pi - 30^\circ)}{\sin(\2\pi + 240^\circ).\cos(2\pi + 300^\circ).\cot(2\pi + 45^\circ)}\)

    \(= \frac{\sec(90^\circ + 30^\circ).\cosec(180^\circ + 30^\circ).-\tan 30^\circ}{\sin(180^\circ + 60^\circ).\cos(360^\circ - 60^\circ).\cot 45^\circ}\)

    \(= \frac{-\cosec 30^\circ. -\cosec 30^\circ. -\tan 30^\circ}{-\sin 60^\circ. \cos 60^\circ.\cot 45^\circ}\)

    \(= \frac{2.2.\frac{1}{\sqrt{3}}}{\frac{\sqrt{3}}{2}.\frac{1}{2}.1}\)

    \(= \frac{16}{3}\)

  57. L.H.S. \(\cos^630^\circ + \sin^6 30^\circ = \left(\frac{3}{2}\right)^6 + \frac{1}{2}^6 = \frac{27}{64} + \frac{1}{64} = \frac{7}{16}\)

    R.H.S. \(= 1 - 3\sin^230^\circ\cos^230^\circ = 1 - 3.\frac{1}{2^2}.\frac{3}{2^2} = 1 - \frac{9}{16} = \frac{7}{16}\)

    Thus, L.H.S. = R.H.S.

  58. L.H.S. \(= \left(1 + 1 + \sqrt{2}\right)(1 + 1 - {\sqrt{2}) = 4 - 2 = 2 = \cosec^245^\circ\)

59 and 60 are similar to 52 and 51 respectively and have been left as an exercise.

  1. L.H.S. \(= \sin^2 \frac{\pi}{18} + \sin^2\frac{2\pi}{18} + \ldots + \sin^2\frac{9\pi}{18}\)

    \(\sin^2\frac{8\pi}{18} = \sin^2\left(\frac{\pi}{2} - \frac{\pi}{18}\right) = \cos^2\frac{\pi}{18}\)

    \(\sin^2\frac{7\pi}{18} = \sin^2\left(\frac{\pi}{2} - \frac{2\pi}{18}\right) = \cos^2\frac{2\pi}{18}\)

    Following similarly, the original expression can be written as

    \(\left(\sin^2 \frac{\pi}{18} + \cos^2\frac{\pi}{18}\right) + \left(\sin^2 \frac{2\pi}{18} + \cos^2\frac{2\pi}{18}\right) + \left(\sin^2 \frac{3\pi}{18} + \cos^2\frac{3\pi}{18}\right) + \left(\sin^2 \frac{4\pi}{18} + \cos^2\frac{4\pi}{18}\right) + \sin^2 \frac{\pi}{2}\)

    \(= 5 =\) R.H.S.

  2. \(2n\alpha = \frac{\pi}{2}\)

    L.H.S. \(= \tan\alpha\tan2\alpha\tan3\alpha. \ldots .\tan(2n - 2)\alpha\tan(2n - 1)\alpha\)

    \(= \tan\alpha\tan2\alpha\tan3\alpha. \ldots .\cot2\alpha.\cot\alpha\)

    \(= 1 =\) R.H.S.